Impact of country-specific business integrity and firm-specific ESG on earnings quality : evidence from EU civil law jurisdictions - Lindahl Frederick; Kantola Satu-Päivi; Schadewitz Hannu (Emerald, 2025)
Purpose
This paper aims to examine whether variations in country-specific business integrity (BI) and firm-specific environmental, social and governance (ESG) dimensions can explain variations in earnings quality (EQ) in Northern and Southern EU civil law countries.
Design/methodology/approach
Regarding EQ, the analysis builds on the “small gain, small loss” (SGSL) model of Burgstahler and Dichev (1997) and Burgstahler and Chuk (2015). The authors explain SGSL with the BI. Southern Europe or “Club Med” is typically associated with a less rigorous institutional regime than Northern Europe.
Findings
Results evidenced higher EQ in the Northern EU compared with the Southern EU. Furthermore, EQ is explained successfully with the Business Integrity Index (BII) and ESG. The results suggest that BII and ESG represent different dimensions, and, therefore, both should be included in the models explaining EQ.
Practical implications
The results show that the Northern EU civil law countries have higher EQ compared with the Southern EU civil law countries. The difference is explained by the BII variable. For the Southern EU, legislators and other public policy decision-makers should build up and apply tools to limit and fight corruption in those jurisdictions. The impactful elimination of corruption would, in turn, establish a firmer basis to foster ethical behavior and financial market sophistication developments.
Originality/value
The study offers additional insights on the determinants of EQ in the EU civil law countries. The prior literature has argued that, categorically, in common law countries firms engage in higher-quality reporting than those in civil law countries. The results evidence that EQ varies within the EU civil law countries; that is, a country’s BI and firm-specific ESG contribute to the explanation for EQ. A more specific explanation for the reasons in the EQ “within” civil law jurisdictions could be related to legislators and other public policy decision-makers in charge of establishing regimes and public policies supporting high-quality accounting.